Conceptualizing business-to-thing interactions – A sociomaterial perspective on the Internet of Things. Issue 4 (4th July 2018) - Oberländer, Anna Maria; Röglinger, Maximilian; Rosemann, Michael; Kees, Alexandra
Abstract: The Internet of Things (IoT) is recognised as one of the most disruptive technologies in the market as it integrates physical objects into the networked society. As such, the IoT also transforms established business-to-customer interactions. Remote patient monitoring, predictive maintenance, and automatic car repair are examples of evolving business-to-thing (B2T) interactions. However, the IoT is hardly covered by theoretical investigations. To complement the predominant technical and engineering focus of IoT research, we developed and evaluated a taxonomy of B2T interaction patterns. Thereby, we built on sociomateriality as justificatory knowledge. We demonstrated the taxonomy's applicability and usefulness based on simple and complex real-life objects (i.e., Nest, RelayRides, and Uber). Our taxonomy contributes to the descriptive knowledge on the IoT as it enables the classification of B2T interactions and facilitates sense-making as well as theory-led design. When combining weak and strong sociomateriality, we found that the IoT enables and requires a new perspective on material agency by considering smart things as independent actors.